Judges' Legal Considerations Obstacles Of Justice By Advocates Make It Difficult In Investigations, Prosecutions And Judicial Processes Against Defendants In Corruption Crimes - M Ridwan; Saut Parulian Panjaitan; Ruben Achmad (Fakultas Hukum Dehasen, 2024)
The aim of this research is to analyze law enforcement related to obstruction of justice and juridical responsibility if lawyers (advocates) deliberately obstruct investigations, investigations and prosecution processes: The method of this research is normative legal research with an approach used by regulations (laws). Statutory Approach), Case Approach. Analysis of legal materials uses qualitative analysis and deductive conclusion drawing. Research Results Factors that influence law enforcement related to obstacles to justice in prosecution for criminal acts of corruption include: The legal substance factor, namely that Article 21 of the Corruption Eradication Law does not clearly regulate prohibited acts. Article 21 only states